2008
DOI: 10.1007/s10712-008-9033-3
|View full text |Cite
|
Sign up to set email alerts
|

Hydrological Signals Observed by the GRACE Satellites

Abstract: The main objective of the US-German twin-satellite mission GRACE (Gravity Recovery and Climate Experiment), launched in March 2002, is a precise survey of the Earth's time-variable gravity field at unprecedented temporal and spatial scales. Temporal changes in the gravity field are related to continuous mass redistributions near the Earth's surface which are caused by various geophysical and climatologically driven processes. Vice versa, transferring the GRACE-based gravity variations into time series of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
98
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 142 publications
(100 citation statements)
references
References 45 publications
2
98
0
Order By: Relevance
“…Schmidt et al (2008aSchmidt et al ( , 2008b provide a near complete survey of this type of research and the state of the art in hydrological applications of GRACE. Hydrological models have been the main source of validation for GRACE applications to hydrology.…”
Section: Comparisons In Terms Of Global Hydrologymentioning
confidence: 99%
“…Schmidt et al (2008aSchmidt et al ( , 2008b provide a near complete survey of this type of research and the state of the art in hydrological applications of GRACE. Hydrological models have been the main source of validation for GRACE applications to hydrology.…”
Section: Comparisons In Terms Of Global Hydrologymentioning
confidence: 99%
“…In a recent study tailored towards the requirements of hydrological applications, Werth et al 2008 concluded that optimum filter types and parameters vary from river basin to river basin, depending on its geographical location, its shape, and the characteristics of the hydrological signals in and around the basin of interest. Estimating errors for GRACE data of continental water storage change is a major challenge for ongoing GRACE processing activities (Schmidt et al 2008b) and could not fully be achieved so far because no ground truth data sets on water storage with sufficiently large spatial extent, homogeneity and support (e.g. station density and monitoring coverage of all water storage compartments) exist.…”
Section: Grace Data Of Continental Water Storage Changementioning
confidence: 99%
“…The independent knowledge of these atmospheric and oceanic mass transport components is also needed in order to separate individual contributions from the GRACE gravity models and, for example, to extract hydrological (e.g. Rodell & Famiglietti 2001;Ramillien et al 2004;Schmidt et al 2008) or glaciological signals (e.g. Horwath & Dietrich 2009;Groh et al 2014).…”
Section: Introductionmentioning
confidence: 99%